A Dual‐FRET‐Based Versatile Prodrug for Real‐Time Drug Release Monitoring and In Situ Therapeutic Efficacy Evaluation. (5th November 2015) - Li, Shi‐Ying; Liu, Li‐Han; Rong, Lei; Qiu, Wen‐Xiu; Jia, Hui‐Zhen; Li, Bin; Li, Fei; Zhang, Xian‐Zheng
Abstract : A dual‐Förster resonance energy transfer (FRET)‐based versatile prodrug (V‐prodrug), in which the fluorescence of both 5(6)‐carboxylfluorescein (FAM) and doxorubicin (DOX) can be quenched by 4‐(dimethylaminoazo)benzene‐4‐carboxylic acid (Dabcyl) with high quenching efficiency, is developed in this paper. The V‐prodrug can selectively bind to the αv β3 integrin overexpressed cancer cells through the Arg‐Gly‐Asp (RGD) targeting moiety. After that, the acid‐mediated DOX release of the V‐prodrug can be real‐time monitored by the increase of the red fluorescence from DOX. Thereafter, DOX‐induced cell apoptosis can also be in situ assessed by the fluorescence recovery of the FAM, due to the caspase‐3‐mediated Asp‐Glu‐Val‐Asp (DEVD) peptide sequence cleavage. This novel prodrug provides a cascaded imaging of real‐time drug release and subsequent cell apoptosis, which enables the in situ detection of the cancer response and the therapeutic efficacy evaluation of the prodrug. Abstract : A dual‐Förster resonance energy transfer (FRET)‐based versatile prodrug (V‐prodrug) is designed to provide a cascaded imaging of real‐time drug release and subsequent cell apoptosis. This V‐prodrug enables the in situ detection of the cancer response as well as the therapeutic efficacy evaluation of the drug.